On university programmes and market demand - Moreiro-González, José-Antonio (Anuario ThinkEPI, 2015)
Two closely related aspects of the information and documentation sector -university education and labour market- are discussed. We consider the equivalencies and transferability of previous courses and degrees for credit towards the Information and Documentation degree, and some possible effects of the new three-year degrees. In relation to the labour market in our sector, we discuss the opacity of our contribution to the digital content economy. Summarized in tables, the most striking results of our analysis of employment and unemployment rates and types of job openings posted in information and documentation in 2014 are presented and discussed.
Keywords: Schools; University; Information and documentation; Information science; Graduate studies; Information professionals; Librarians; Librarianship; Homologations; Accreditations; Equivalences; Threeyear degrees; Labour market; New contracts; Evolution of une